I︠U︡gorskiĭ Shar / Sostavleno v 1922 g. po robotam Gidrograficheskikh ėkspedit︠s︡iĭ Severnogo Ledovitogo okeana v 1898 - 1920 g. g. - Soviet Union. Gidrograficheskoe upravlenie; (Petrograd : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenie SSSR; [Петроград] : Морское министерство, Главное гидрографическое управление СССР, 1923)
Relief shown by hachures. Depths shown by soundings and isolines.; Main title translation: Yugor Strait.; Top margin title translation: Arctic Ocean, Kara Sea.; Includes notes and illustrations.; Greenwich meridian.; "Masshtab 1/72960 ili 1 mili︠a︡ v di︠u︡ĭme po paralleli 69°40'." = Scale 1/72960 or 1 mile in 1 inch on the 69°40' parallel.; "Sostavleno v 1922 g. po robotam Gidrograficheskikh Ėkspedit︠s︡iĭ Severnogo Ledovitogo okeana v 1898 - 1920 g. g." = Compiled in 1922 according to the work of the Hydrographic Expedition of the Arctic Ocean of 1898 - 1920.; "No. 576" -- margins Color; 1:72,960